Smart Autoplanter: Automatic Plant Cultivation System - Zulkifly Ngin, Hendry Firmansah; Mohd. Yasin, Suhaila; Ismail, Suhaida (Applied Information Technology And Computer Science, 2025)
This project aims to address the inefficiencies in cultivating plants, especially in urban areas. The Smart Autoplanter is a system that provides a way to automate plant cultivation, like watering and fertilization needs and plan harvest schedules. In addition, the system’s objective is to design and develop a working prototype and have it tested to meet the user’s expectation. The system’s modules manages the planter , gardening routine , harvest planning , custom plant cultivation and modular gardening . By implementing this system, the project aims to reduce the plants’ tending and nurturing period in urban settings, and enhance their cultivation while providing a way for users to learn along the way. The chosen methodology for this project is the Prototyping model, which includes iterative development, user feedback and continuous improvement. This project provides an innovative approach to urban gardening trend that is in line with rapidly evolving automation technologies.